Field and pilot-scale geochemical investigations into using sewage sludge for sulphidic mine waste remediation - Nason, Peter (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2012)
Successful mine waste reclamation is a fundamental aspect in mine plan development and is legislated through the European Parliament’s ‘Management of Waste from Extractive Industries Directive (2006/21/EC)’. Field and pilot-scale trials were utilised to evaluate different applications of an alternative cover material, sewage sludge, in its ability to remediate and prevent acid rock drainage formation from sulphidic mine tailings derived from the Kristineberg Zn-Cu mine, northern Sweden. Sewage sludge is an organically-rich waste material generated from the treatment of domestic waste water. It may function suitably as a low permeable barrier against oxygen ingress when compacted or as a surface vegetation substrate. The first study focused on evaluating the effectiveness of a sewage sludge sealing layer, part of a composite dry cover design system. Data on tailings, leachate water and pore gas geochemistry during eight years from two experimental pilot-scale test cells revealed that the sludge was an effective barrier to oxygen influx, which prevented sulphide oxidation and acid rock drainage formation. Sludge-borne metals (Cd, Co, Cu, Fe, Pb, Zn) precipitated and were retained in the underlying tailings due to the reduced conditions produced, resulting in low concentrations of dissolved metals (<10μg/L Cd, Co, Cu, Ni, Pb, Zn) in the drainage, several orders of magnitude lower than that from an uncovered tailings reference cell. However, a 19.6% mass reduction of the sludge due to organic matter degradation may compromise the effectiveness of the cover in the long-term. The second study evaluated the geochemical impact of a field-scale surface application of sewage sludge on the groundwater quality of a formally-remediated sulphidic-tailings impoundment. Thirteen years after initial remediation, 12 000 tonnes of sludge were applied to a depth of 0.3m to re-vegetate and stabilise the pre-existing water-saturated and composite dry cover design systems. After two years, a 17% reduction of the sludge volume ...